Whipworm kinomes reflect a unique biology and adaptation to the host animal. Issue 13 (November 2017) - Stroehlein, Andreas J.; Young, Neil D.; Korhonen, Pasi K.; Chang, Bill C.H.; Nejsum, Peter; Pozio, Edoardo; La Rosa, Giuseppe; Sternberg, Paul W.; Gasser, Robin B.
Graphical abstract: Highlights: First known comprehensive curation and functional annotation of kinase genes encoded in genomes of two whipworm species. Detailed analysis of transcription of kinase genes in different life cycle stages and tissues for Trichuris suis. Substantial differences in kinomes between enoplean and chromadorean nematodes. Adaptations in kinomes reflect environmental signalling processes and host–parasite interactions. Abstract: Roundworms belong to a diverse phylum (Nematoda) which is comprised of many parasitic species including whipworms (genus Trichuris ). These worms have adapted to a biological niche within the host and exhibit unique morphological characteristics compared with other nematodes. Although these adaptations are known, the underlying molecular mechanisms remain elusive. The availability of genomes and transcriptomes of some whipworms now enables detailed studies of their molecular biology. Here, we defined and curated the full complement of an important class of enzymes, the protein kinases (kinomes) of two species of Trichuris, using an advanced and integrated bioinformatic pipeline. We investigated the transcription of Trichuris suis kinase genes across developmental stages, sexes and tissues, and reveal that selectively transcribed genes can be linked to central roles in developmental and reproductive processes. We also classified and functionally annotated the curated kinomes by integrating evidence from structural modelling and pathway analyses, and compared them with other curated kinomes of phylogenetically diverse nematode species. Our findings suggest unique adaptations in signalling processes governing worm morphology and biology, and provide an important resource that should facilitate experimental investigations of kinases and the biology of signalling pathways in nematodes.